2015
DOI: 10.2147/jpr.s86573
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prevalence of autoimmune, endocrine, gynecologic, and psychiatric comorbidities in an ethnically diverse cohort of female fibromyalgia patients: does the time from hysterectomy provide a clue?

Abstract: BackgroundThis retrospective chart review investigated differences in the prevalence of medical comorbidity between women with fibromyalgia (FM) (n=219) and a control group women with chronic pain (CP) without FM (n=116). The specific aims were to compare the prevalence of autoimmune, psychiatric, endocrine, gynecologic pathology, the relationship between timing of gynecologic surgery, and pain onset. We additionally sought to compare the number of comorbidities in an ethnically diverse cohort.MethodsThis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…These data suggest a relationship between fibromyalgia and these pathologies and, by extrapolation, infertility. They are also in agreement with the data of [39] that showed a high prevalence of gynecological, endocrine and autoimmune diseases in women with fibromyalgia. The dysfunction of the hypothalamic-pituitary axis is generally associated to fibromyalgia as well as to gynecological and endocrine pathologies [40], thus suggesting a comorbidity with fibromyalgia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data suggest a relationship between fibromyalgia and these pathologies and, by extrapolation, infertility. They are also in agreement with the data of [39] that showed a high prevalence of gynecological, endocrine and autoimmune diseases in women with fibromyalgia. The dysfunction of the hypothalamic-pituitary axis is generally associated to fibromyalgia as well as to gynecological and endocrine pathologies [40], thus suggesting a comorbidity with fibromyalgia.…”
Section: Discussionsupporting
confidence: 92%
“…One of the main factors is hormonal disorders (female hormones and high male hormone levels). It is well known that gynecological and endocrine pathologies are commonly observed in fibromyalgia patients [39]. The diagnosis of fibromyalgia in patients with ovarian cysts is therefore not surprising.…”
Section: Discussionmentioning
confidence: 99%
“… 5 10 Symptom presentation varies greatly between individuals, with a wide variety of clinical, physical, social, and psychological repercussions and of therapeutic responses. Studies on FM pathophysiology report hyperalgesia to experimental stimuli, 10 , 11 14 central nervous system abnormalities and cerebral changes, 15 19 autonomic and neuroendocrine system abnormalities, 20 genetic factors, 21 and microbiota specificities. 22 …”
Section: Introductionmentioning
confidence: 99%
“…The exact etiology of FMS is unknown, and the pathogenesis involves psychology, environmental, genetics, hormonal (serotonin), and impaired sleep quality. Brooks et al ( 12 ) found that gynecologic, endocrine, and autoimmune diagnoses were associated with a diagnosis of FMS. They also found a relationship between the timing of gynecologic surgery and pain onset in FMS.…”
Section: Discussionmentioning
confidence: 99%